THEMATIC ANALYSIS OF SELECTED NOVELS OF RAJA RAO: AN OVERVIEW - Verma, Minaxi; Dubey, Neeraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Literature is the mirror to society. It reflects the people, the lifestyle, culture, religion, traditions, trends, and practices of the contemporary world. Raja Rao, a doyen of Indian English literature, is viewed as a philosopher who emphasizes the spirit of India with the modernity of the world. The paper will carry out a thematic analysis of some select novels of Raja Rao with a view to exploring how Raja Rao’s works reflect India’s socio-cultural milieu, spiritual traditions, and the human quest for meaning. In such novels as Kanthapura and The Serpent and the Rope, Rao unravels the synthesis of Indian metaphysical thought with its adverse swing towards modernity. Kanthapura evokes the intricate joining of India’s struggle for independence with Gandhian ideals of communal unity, non-violence, and the strength of rural India, while The Serpent and the Rope covered the gamut on questions of identity, spirituality, and the search for self-realization that draws heavily from Advaita philosophy. This paper also tries to understand how the works of Raja Rao have brought out the tension between tradition and modernity, showing the cultural dilemma of post-colonial India. His depiction of the character’s inner struggle, his spiritual pursuit, and relationship with Indian traditions reflect his intense involvement with India’s philosophical traditions. Besides, the employment of myth, folklore, and oral traditions in his narratives gives added dimensions to his engagement with questions of identity, nationalism, and existentialism. The paper thematically explicates these novels with the view of establishing Raja Rao’s contribution to Indian English literature and his role in shaping modern Indian thought, especially in the post-colonial era. His novels stand as a testimony to the continuing dialogue between the past of India and the variously emerging present of the country.